Valuation of economic benefits from the Finnish salmonella control program - Peltola, Jukka; Aakkula, Jyrki; Maijala, Riitta; Siikamäki, Juha (MTT, 2001)
The This paper examines consumer benefits of the Finnish Salmonella Control Program (FSCP) by using a contingent valuation survey method. The survey aimed at measuring consumers' willingness to pay (WTP) for Finnish salmonella control program. Based on the survey results, consumers are willing to spend an additional 20-50 FIM (or roughly 3.3-8.3 EUROs) per month to finance the current level salmonella control in food of animal origin in Finland. This transforms to an annual payment of 420 FIM or about 70 EUROs, which in turn can be taken as a measure of benefits from the current salmonella control program. In comparison to the cost of the program, the benefits are relatively large, and FSCP is therefore considered beneficial from the economic viewpoint. According to the analysis, consumers' concern about the salmonella situation in Finland motivates their WTP for the FSCP. Previous encounter(s) with food poisoning did significantly influence the WTP. An Economic Assessment of Effects of the Finnish Salmonella Control Program on Trade Jukka Peltola1 Abstract. In this paper, indirect costs of the Finnish Salmonella Control Program (FSCP) are evaluated. Traditional welfare analysis is used for analyzing the changes in consumers' and producers' welfare due to the program. FSCP could, by its very structure, act as a technical trade barrier and thus hinder international trade (food imports to Finland). According to a theoretical analysis, potential welfare losses due to decreased trade flows are possible. However, empirical calculations do not lend support to significant trade losses as nearby countries, practicing large scale food exporting, have prices of food stuffs approximately on the same level as Finnish prices. That suggests, that the program does not greatly affect the trade. In case of pork, some potential effects can be found, however, their real significance is questionable, and direct reasons behind cost dissimilarities cannot be exactly determined. Index words: food safety, salmonella control, safeguard policy, welfare analysis
Keywords: Ma; elintarviketurvallisuus; salmonella; elintarvikkeet; turvallisuus; terveys; talous; food safety; health; salmonella; valuation; salmonella control; contingent valuation; non-market valuation